Structure-based targeting of orthologous pathogen proteins accelerates antiparasitic drug discovery - Jain, V; Sharma, A; Singh, G; Yogavel, M; Sharma, A (American Chemical Society, 2017)
Parasitic diseases caused by eukaryotic pathogens impose significant health and economic burden worldwide. The level of research funding available for many parasitic diseases is insufficient in relation to their adverse social and economic impact. In this article, we discuss that extant 3D structural data on protein–inhibitor complexes can be harnessed to accelerate drug discovery against many related pathogens. Assessment of sequence conservation within drug/inhibitor-binding residues in enzyme–inhibitor complexes can be leveraged to predict and validate both new lead compounds and their molecular targets in multiple parasitic diseases. Hence, structure-based targeting of orthologous pathogen proteins accelerates the discovery of new antiparasitic drugs. This approach offers significant benefits for jumpstarting the discovery of new lead compounds and their molecular targets in diverse human, livestock, and plant pathogens.